Prevalence and types of errors in the electronic health record: protocol for a mixed systematic review - Cosima Locher; Maria Hägglund; Brian McMillan; Ylva Trolle Lagerros; Charlotte Blease; Josefin Hagström; Anna Kharko; Joanne Hunt; Kirralise Hansford; Dafina Angelova; Therese Scott Duncan; Asha-Judy Nivins; et al. (BMJ Open)
Introduction In countries with access to the electronic health record (EHR), both patients and healthcare professionals have reported finding errors in the EHR, so-called EHRrors. These can range from simple typos to more serious cases of missing or incorrect health information. Despite their potential detrimental effect, the evidence on EHRrors has not been systematically analysed. It is unknown how common EHRrors are or how they impact patients and healthcare professionals.Methods and analysis A mixed systematic review will be carried out to address the research gap. We will search PubMed, Web of Science and CINAHL for studies published since 2000, which report original research data on patient-identified and healthcare professional-identified EHRrors. We will analyse (1) the prevalence of EHRrors, (2) the types of EHRrors and (3) their impact on care. Quantitative and qualitative findings will be synthesised following the Joanna Briggs Institute Framework for Mixed Systematic Reviews. Identified studies will be critically appraised for meta-biases and risk of bias in individual studies. The confidence in the emerging evidence will be further assessed through the Grading of Recommendations Assessment, Development and Evaluation approach. Findings will be contextualised and interpreted involving an international team of patient representatives and practising healthcare professionals.Ethics and dissemination The study will not involve collection or analysis of individual patient data; thus, ethical approval is not required. Results will be published in a peer-reviewed publication and further disseminated through scientific events and educational materials.PROSPERO registration number CRD42024622849.